STRATEGI INOVASI SOSIAL PENGEMBANGAN MUTU SUMBER DAYA MANUSIA NELAYAN - Wildani Pingkan S. Hamzens; Sumardjo Sumardjo (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2007)
From generation to generation fisherman has been making a live for himself and family mainly by extracting coastal and marine resources. There are a number of program development designed to promote fisherman quality of life. However, there is still little progress in fisherman living quality. As the consequences, their ability to suffice their own and family needs also low. The objectives of this research are.- (1) to explain and analyze, condition of fisherman resources quality based on competence, ability to fulfill consumer's need, income, and ability to suffice their own and their family need; and (2) to formulized effective fisherman resource quality enhancement strategy. Research has shown that: (1) low qualiy of fisherman resource, reflected on: low competence, low ability to fulfill needs, low income, low ability to suffice their own and their family needs for living; (2) Fisherman resource quality enhancement strategy divided on: (a) internal strategy, by applying social inovation through continuous non formal education (extension,) and (b) external strategy by increasing environment supports for fisherman effort according to their need.